Pelaksanaan Program Posyandu Dalam Meningkatkan Kesejahteraan Ibu Dan Anak (Studi Di Desa Labaraga Kecamatan Wakorumba Utara Kabupaten Buton Utara) - Fira, Wa; Batara, Suriyani Bunga; Purwati, Ninik Endang (Universitas Halu Oleo, 2021)
This study aims to identify and understand the causes of implementing the posyandu program in improving the welfare of mothers and children and the obstacles in implementing the posyandu program in improving the welfare of mothers and children in Labaraga Village. This type of research is qualitative, using several informants to conduct interviews and observations. Sources of data used are primary data sources, namely information that comes from direct observation to the research location by means of observation and interviews. Meanwhile, secondary sources are data obtained from documents held by posyandu cadres to complement primary data. Data collection was carried out through observation, interviews and documentation. The results showed that the implementation of the posyandu program in improving the welfare of mothers and children in Labaraga Village, namely: socialization, counseling and assistance. Meanwhile, the posyandu cadres' obstacles in improving the welfare of mothers and children in Labaraga Village, North Wakorumba District, North Buton Regency, namely: obstacles from the Human Resources aspect, obstacles to facilities and infrastructure and obstacles in the implementation process.